My first Prophet Muhammad (SAW) storybook - Khan, Saniyasain (UAE : Goodword Books, 2024)
My First Prophet Muhammad (S.A.W) Storybook introduces young children to the life and teachings of Prophet Muhammad (S.A.W) through simple language and colorful illustrations. The stories focus on his kindness, honesty, and compassion, helping children understand Islamic values and moral lessons from an early age. Designed for beginner readers, it encourages love for the Prophet and inspires good character in daily life.
Keywords: Islam - non-fiction book